Association Between Accelerated Multimorbidity and Age-Related Cognitive Decline in Older Baltimore Longitudinal Study of Aging Participants without Dementia - Fabbri, Elisa; An, Yang; Zoli, Marco; Tanaka, Toshiko; Simonsick, Eleanor M.; Kitner-Triolo, Melissa H.; Studenski, Stephanie A.; Resnick, Susan M.; Ferrucci, Luigi (Journal of the American Geriatrics Society (JAGS), 2016)
Objectives To explore the association between rate of physical health deterioration, operationalized as rising multimorbidity overtime, and longitudinal decline in cognitive function in older adults without dementia. Design Longitudinal (Baltimore Longitudinal Study of Aging (BLSA)). Setting Community. Participants BLSA participants aged 65 and older followed for an average of 3 years and free of dementia or mild cognitive impairment (MCI) at baseline and follow‐up (N = 756). Measurements Standardized neurocognitive tests evaluating mental status, memory, executive function, processing speed, and verbal fluency were administered. Multimorbidity was assessed at each visit as number of diagnosed chronic diseases from a predefined list. Faster accumulation of chronic diseases was defined as upper quartile of rate of change in number of diseases over time (≥0.25 diseases/year). Results Faster accumulation of chronic diseases was significantly associated with greater rate of decline on the Category (P = .01) and Letter (P = .01) Fluency Tests. Similar trends were also found for the Trail‐Making Test Parts A (P = .08) and B (P = .07); no association was found with rate of change in visual and verbal memory. Conclusion Although further investigations are required to validate the results and fully understand the underlying mechanisms, these findings suggest that accelerated deterioration of physical health is associated with accelerated decline with aging in specific cognitive domains in older adults without dementia.